Some Information About the Names of The Mosque Located in Margilan - Akhmedova Mashhurakhon Ulugbek qizi (Zien Journals, 2021)
This article provides a brief overview of the science of toponymy, the names of some mosques in the city of Margilan, Fergana region, as well as the views of scholars on the toponym Kirguli.
Keywords: eclectic; toponym; onomastics; mosque name